Case report: Noonan syndrome with protein-losing enteropathy - Ou, Yang; Yuan, Jun-Chao; Zheng, Yao; Zhang, Jin-Man; He, Tian; Liang, Zhi; Zhou, Yi-Kun (Frontiers in Genetics, 2023)
Background: Noonan syndrome (NS) is characterized by typical facial features, short stature, congenital heart defects and other comorbidities. Lymphedema and chylous pleural effusions are also common in NS, but protein-losing enteropathy (PLE) is rarely reported. Case presentation: We present the case of a 19-year-old Chinese woman presenting with PLE. Small intestine biopsy showed obvious expansion of lymphatic vessels. The gene mutation results of the patient indicated a c.184T>G missense mutation (p.Tyr62Asp) in the PTPN11 gene (NM_002834.3). Conclusions: NS accompanied by PLE is not common, but hypoproteinemia attributable to PLE may be more common in patients with NS than previously thought. It remains uncertain whether mutation of the PTPN11 gene is related to PLE, indicating that further research is needed.